Studi Numerik Pengaruh Penggunan Splitter Plate Terhadap Sifat Aliran di Sekitar Penampang Persegi - Yanto, Andi; Barata, La Ode Ahmad; Endriatno, Nanang (Teknik Mesin Universitas Halu Oleo, 2023)
The phenomenon of the movement of fluid flow across an object plays an important role in terms of transportation. Different body shapes will produce different fluid flow characteristics and greatly affect the function of the body shape, so it is important to know the characteristics of fluid flow, so that the factors causing losses in a construction that are not in accordance with the natural properties of the fluid can be identified. If the drag is large can be reduced, the energy needed to move can be reduced and save fuel. the use of numerical methods is a way of studying flow characteristics that is relatively inexpensive with a scientifically justifiable level of accuracy. The problem of this study is how the characteristics of the fluid flow to the forces that pass through the square cross section. This study uses a square geometry test model and a single splitter plate geometry test. The research was carried out by computational methods using Ansys FLUENT CFD software with the Realizable k-ε turbulence model. The results showed that the use of a splitter plate resulted in a decrease in Cd, -CPb values and an increase in speed (u). This indicated that the use of a splitter plate could reduce resistance and pressure and expedite the distribution of fluid flow. and there is an increase in the Cl value parameter, this is due to the enlargement of the wake. From this study it was found that the use of a splitter plate was good in reducing Cd values, this is in accordance with the literature Kata kunci: Ansys fluent, CFD, fluid, Reynolds, drag coefficient, pressure coefficient, lift coefficient